Implementation of Character Education Cultivation Through Uwais Alqarni Character Film in Banu Thurayya Kindergarten - Shifani, Laila; Zulfahmi, Muhammad Nofan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Character education is an important aspect in children's personal formation. Good character includes not only academic knowledge, but also positive moral, ethical, and personality values. One effective way to instill character education in children is through the use of visual media, such as movies. The purpose of this study was to investigate the impact of the use of visual media, especially the film character Uwais Alqarni, in character learning in Banu Thurayya Kindergarten. This research will explore the extent to which the film is effective in shaping positive values, as well as identifying and detailing potential problems that arise in its application. The method used in this study is qualitative with a descriptive analysis approach. The results of this study show that the implementation of character education cultivation through the film character Uwais Alqarni in Banu Thurayya Kindergarten is an innovative and effective step. Through this approach, children can learn in a fun and interactive way, while gaining a deep understanding of the positive values in Islam. The influence of visual media, especially through the film character Uwais Alqarni, in character education in K TK Banu Thurayya brought a striking positive impact. The film provides an immersive visual portrayal of Islamic values and moral character, creating an immersive and meaningful learning experience for children. Through the appeal of visual stories, children not only gain knowledge about Islamic teachings, but also permeate these values through the behavioral model of the character Uwais Alqarni